The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-63518-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced methane-bearing fluids as a source for diamond

Abstract: Diamond formation in the Earth has been extensively discussed in recent years on the basis of geochemical analysis of natural materials, high-pressure experimental studies, or theoretical aspects. Here, we demonstrate experimentally for the first time, the spontaneous crystallization of diamond from CH 4-rich fluids at pressure, temperature and redox conditions approximating those of the deeper parts of the cratonic lithospheric mantle (5-7 GPa) without using diamond seed crystals or carbides. In these experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Notably, methane-rich fluids have recently been shown to generate pure carbon in the form of diamond under very high pressure (5 to 7 GA) ( 51 ). This process occurs by the removal of hydrogen from methane:…”
Section: Discussionmentioning
confidence: 99%
“…Notably, methane-rich fluids have recently been shown to generate pure carbon in the form of diamond under very high pressure (5 to 7 GA) ( 51 ). This process occurs by the removal of hydrogen from methane:…”
Section: Discussionmentioning
confidence: 99%
“…Observations of CH 4 in diamonds are rare (Smit et al 2016) and growth from CH 4 , or CH 4 -H 2 O low-density fluids was suggested based on modeling of isotopic fractionation (e.g., Thomassot et al 2007;Smit et al 2019). Experimental studies found that "in oxidized fluids (CO 2 ; CO 2 -H 2 O; H 2 O), the intensity of spontaneous nucleation, the rate of diamond growth on seed crystals, and the degree of graphite-diamond transformation are considerably higher than those in reduced fluids (H 2 O-CH 4 ; CH 4 -H 2 )" (Palyanov et al 2015), but a recent study does suggest nucleation and growth of diamond in the harzburgite+CH 4 system (Matjuschkin et al 2020). Smith et al (2016) reported the finding of iron-nickel-carbon-sulfur inclusion in lower mantle diamonds, but metallic iron inclusions are known from shallower diamonds as well (Bulanova et al 1998), and this mode of growth may be important and efficient where metallic melts exist (e.g., below 250 km, Frost and McCammon 2008).…”
Section: High-density Fluids and Diamond Formationmentioning
confidence: 98%
“…Diamond growth is characterised by temperature-dependent induction times, certainly for nucleation of new diamond crystals, and in some cases even for growth on pre-existing seed diamonds. More recent studies such as Matjuschkin et al (2020) have demonstrated the ability of these fluids to grow diamonds at lower temperatures (e.g., that are more realistic for lithospheric mantle geotherms). In this study, extensive efforts were devoted to improving experimental design to minimize changes in fluid composition over the course of the experiments.…”
Section: Overviewmentioning
confidence: 99%